Let’s Eat! Encouraging Self–Feeding Behavior in Waterfowl - Goodman, Michele (Wildlife Rehabilitation Bulletin, 2021)
Waterfowl may not self–feed for a wide variety of reasons including species, food type or presentation, stress, underlying injury or illness, or other husbandry concerns. Understanding natural history, wild diet, and food presentation methods can help to improve self–feeding behavior.